Changes in vascular identity during vascular remodeling - Aoyagi, Yukihiko; Schwartz, Andrew W.; Li, Zhuo; Bai, Hualong; Gonzalez, Luis; Lazcano Etchebarne, Cayetana; Ohashi, Yuichi; Kano, Masaki; Ho, Bryan; Martin, Kathleen; Dardik, Alan (JVS-vascular science, 2025)
Vascular remodeling is a dynamic process characterized by changes in vascular identity that impact vessel structure and function. Molecular markers define cellular identity as arteries, veins, and lymphatic vessels: Ephrin-B2 and Notch determine arterial identity, EphB4 and COUP-TFII determine venous identity, and Prox1 determines lymphatic identity. This is a review of experimental literature. These proteins determine identity during development before the first heartbeat. Hemodynamic changes in adulthood can also alter vascular identity. Changes in identity markers coincide with changes in vascular cell phenotype or disease and thus may play a role in regulating both normal and pathological vascular remodeling. Vascular diseases such as arteriovenous malformations and pulmonary hypertension are driven by changes in cell phenotype and vessel identity. Surgical interventions such as arteriovenous fistula (AVF) creation and arterial bypass using vein grafts induce alterations in identity; vein grafts lose their venous identity, but do not acquire arterial identity, whereas venous limbs of AVF gain arterial identity while retaining their venous identity. After patch angioplasty, vascular patches remodel in their environment. Patches in the venous environment acquire venous identity and patches in the arterial environment develop arterial identity. Interestingly, patches in the venous outflow of AVF gain a mixed venous-arterial phenotype. Changes in vascular identity drive vascular remodeling in both physiological and pathological settings, with potential implications for therapeutic strategies targeting vascular diseases. Vascular remodeling is essential for both physiological and pathological vascular adaptation. Changes in vascular identity occur in response to hemodynamic forces and mediate vascular remodeling during development, in disease states, and after surgical and endovascular interventions. Alterations in arterial and venous molecular markers of identity regulate cellular phenotype, the extracellular matrix, and vessel wall structure, ultimately determining long-term vessel function. Understanding the molecular regulatory pathways controlling vascular identity provides insight into understanding the mechanisms of vascular remodeling and may identify potential therapeutic targets to treat vascular disease and improve outcomes after vascular interventions. [Display omitted]